Penerapan Empat Prinsip Good Governance dalam Pelayanan Publik di Dinas Kearsipan dan Perpustakaan Provinsi Gorontalo - Friska Nuriman Muchsin; Zuchri Abdussamad; Irawaty Igirisa (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to analyze the implementation of four principles of Good Governance in an effort to improve the quality of public services at the Archives and Library Service of Gorontalo Province. The method used in this study is a descriptive research method with a qualitative approach, involving various stakeholders in the process. The results of the study indicate that the implementation of the principles of Good Governance in the Archives and Library Service of Gorontalo Province has been running well. Accountability is reflected through standard operating procedures (SOPs), effective supervision, information disclosure, and active public participation, while transparency is supported by the iArpus application and the SAKTI Card program, which allow for more accessible public access. The principle of the rule of law is consistently applied through regulations, personnel regulations, and the latest Governor's Regulation, ensuring that services become orderly and directed. Although follow-up to public input still needs to be accelerated, overall, the service demonstrates a strong commitment to professional, modern, and responsible public services.